Using the Condylar Prosthesis After Resection of a Large Odontogenic Myxoma Tumor in the Mandible - Melo, Willian Morais de [UNESP]; Pereira-Santos, Darklilson; Breda, Marcus Antonio; Sonoda, Celso Koogi [UNESP]; Hochuli-Vieira, Eduardo [UNESP]; Serra e Silva, Fabricio Moreira (Lippincott Williams & Wilkins, 2012)
Odontogenic myxomas are considered to be a benign odontogenic tumor with locally aggressive behavior. Because these neoplasms are rare in the oral cavity, the possible surgical management can be quite variable. Literature recommendation can vary from simple curettage and peripheral ostectomy to segmental resection. The authors report a case of a 20-year-old patient with an odontogenic myxoma tumor located in the left mandibular angle, ascending ramus, and mandibular symphysis. It was treated by radical resection followed by titanium reconstruction with condylar prosthesis, which allowed rapid return of function with improvement in quality of life and restoration of cosmetic and functional deficits. The lesion did not recur after surgical procedure.
Keywords: Odontogenic myxoma; mandible; reconstruction; surgical management